THOUGHTS ON THE HISTORY OF FORMATION OF MEDICAL TERMS - G. SH. Doniyorova (American Journals, 2022)
The word term was derived from the Latin “terminus” -“limit”, “border”and give the exact designation of objects, concept, processes in certain field of science, for instance in medicine. Terms are the significant part of the language of science. Full definition and stability of use are indispensable requirement for terms. Terminology (from the Latin “terminus”-“term” and Greek “logos” – “word”, “science” is a system of special vocabulary of any scientific discipline, for instance medical terminology. The development of terminology goes hand in hand with the development of science, since each new concept must be fixed by the exact word, term.
Keywords: clinical term, Latin, Greek, concepts, disease.